Comprehensive resistance evaluation of 15 blueberry cultivars under high soil pH stress based on growth phenotype and physiological traits - Yang, Hao; Wu, Yaqiong; Zhang, Chunhong; Wu, Wenlong; Lyu, Lianfei; Li, Weilin (Frontiers in Plant Science, 2022)
High soil pH is one of the main abiotic factors that negatively affects blueberry growth and cultivation. However, no comprehensive evaluation of the high soil pH tolerance of different blueberry cultivars has been conducted. Herein, 16 phenotypic and physiological indices of 15 blueberry cultivars were measured through pot experiments, and the high-pH soil tolerance coefficient (HSTC) was calculated based on these indices to comprehensively evaluate the high-soil-pH tolerance of plants. The results demonstrated that high soil pH stress inhibited blueberry growth, and MDA, soluble sugar (SS), and soluble protein (SP) levels increased in leaves. Moreover, in all cultivars, CAT activity in the antioxidant system was enhanced, whereas SOD activity was reduced, and the relative expression levels of the antioxidant enzyme genes SOD and CAT showed similar changes. In addition, the leaf chlorophyll relative content (SPAD), net photosynthetic rate (Pn), transpiration rate (E), and stomatal conductance (Gs) decreased, while changes in the intercellular CO2 concentration (Ci) were noted in different cultivars. Finally, according to the comprehensive evaluation value D obtained from the combination of principal component analysis (PCA) and membership function (MF), the 15 blueberry cultivars can be divided into 4 categories: high soil pH-tolerant type [‘Briteblue’ (highest D value 0.815)], intermediate tolerance type (‘Zhaixuan 9’, ‘Zhaixuan 7’, ‘Emerald’, ‘Primadonna’, ‘Powderblue’ and ‘Chandler’], low high soil pH-tolerant type (‘Brightwell’, ‘Gardenblue’, ‘Plolific’ and ‘Sharpblue’) and high soil pH-sensitive type [‘Legacy’, ‘Bluegold’, ‘Baldwin’ and ‘Anna’ (lowest D value 0.166)]. Stepwise linear regression analysis revealed that plant height, SS, E, leaf length, Ci, SOD, and SPAD could be used to predict and evaluate the high soil pH tolerance of blueberry cultivars.